(untitled) (Indian Journal of Child Health, 2019)
Background: There are high rates of developmental delay (DD) in children with severe acute malnutrition (SAM). Vitamin B12 is mandatory for the myelination of brain during the early childhood period. Objective: The objective of the study was to find out the percentage of DD in SAM and its association with Vitamin B12 deficiency. Materials and Methods: A prospective, observational study was done in SAM children aged 0–60 months who were admitted in Nutritional Rehabilitation Centre. Developmental assessment was done by Vineland Social Maturity Scale and developmental quotient <70 was considered as DD. Results: DD was found in 55.3% of children. Vitamin B12 deficiency, insufficiency, and sufficiency were found in 14.6%, 24.3%, and 50.5% of children, respectively, and Vitamin B12 level was not significantly associated with DD in children with SAM (p=0.290). Conclusion: More than half of SAM children had DD and it was not significantly associated with Vitamin B12 levels.